Experimental investigation of fish scale reinforced polymer composite. (2020) - Ramesh Babu, K.; Jayakumar, V.; Bharathiraja, G.; Madhu, S.
Abstract: Nowadays various biowaste materials are used as filler material in polymer composites. In this paper, the fish scale which is obtained from the outermost part of fish skin is utilized as filler material. Seven different volume fraction of fish scale were taken with epoxy matrix material to prepare composite plate. The composite specimens were fabricated by hand lay up method. The mechanical properties such as tensile, flexural and impact tests were evaluated as per ASTM standards. The addition of fish scale filler to reinforce the epoxy composite has considerably increased the mechanical properties of the composites. This investigation suggested the possibility of introducing fish scale obtained from the skin of the fish in polymer matrix composites.